Advanced practice nursing : core concepts for professional role development - 4 0 16; 1955- Mirr Jansen, Michaelene P.;Zwygart-Stauffacher, Mary; 5 (New York, New York : Springer Publishing Company, 2010)
Now in its fourth edition, this book remains the key title serving graduate-level advanced practice nurses (APNs) and recent graduates about to launch their careers. The book outlines what is required of the APN, with guidelines for professional practice for each of the four APN roles: the nurse practitioner, clinical nurse specialist, certified nurse midwife, and certified registered nurse anesthetist. Advanced Practice Nursing focuses not only on the care and management of patients, but also on how to meet the many challenges of the rapidly changing health care arena. Obtaining certification, navigating reimbursement, and translating research into practice are just a few of the challenges discussed.--BOOK JACKET.
Overview of advanced practice nursing / Linda Lindeke ... [et al.] -- Advanced practice within a nursing paradigm / Michaelene P. Jansen -- Multifaceted roles of the APN / Mary Zwygart-Stauffacher -- The role of organizations in advanced practice nursing / Mary Zwygart-Stauffacher -- Leadership competencies for APNs : challenges and opportunities / Janet Wessel Krejci and Shelly Malin -- Clinical decision making in advanced practice nursing / Sheila K. Smith -- Health care policy : implications for advanced practice / Linda Reivitz -- Regulation, certification, and clinical privileges / Michaelene P. Jansen -- Practice issues, prescriptive authority, and liability / Michaelene P. Jansen -- Reimbursement realities for advanced practice nurses / Linda Lindeke -- Ethical issues in advanced practice nursing / Karen S. Feldt -- Translating research into practice : barriers and solutions / Kathryn Blair -- Informatics for advanced practice nurses / Jane Peace and Pamela Scheibel -- Scholarship of practice / CeCelia R. Zorn -- Employment strategies for advanced practice nurses / Jennifer Peters -- Launching your career as an advanced practice nurse / Mary Zwygart-Stauffacher and Michaelene P. Jansen.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Nurse practitioners.;Primary care (Medicine);Nurse Clinicians.;Nurse Practitioners.;Nurse Anesthetists.;Nurse Midwives.;Nurse's Role. -- 20; 20; 2